2021
DOI: 10.1007/s12310-021-09454-6
|View full text |Cite
|
Sign up to set email alerts
|

Educator Perspectives of Early Childhood Mental Health: A Qualitative Study in Colorado

Abstract: Mental health problems in early childhood (e.g., depression, anxiety) have a similar prevalence as for older individuals, with 10-15% of preschoolers meeting criteria for clinical diagnosis. Research has shown that intervention to support mental health in early childhood is important to mitigate later problems. However, early intervention is predicated on early identification; by the time young children encounter specialists (e.g., psychologists), problems are often severe. Early childhood educators have the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…This is may be due to fact that rural students have better mental health than male. This finding is in agreement with the finding of the studies by Stein, Rachel(2021). The finding of present study shows that there is no significant difference among arts, science and Mathematics student's teacher in their mental health.…”
Section: Interpretation and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is may be due to fact that rural students have better mental health than male. This finding is in agreement with the finding of the studies by Stein, Rachel(2021). The finding of present study shows that there is no significant difference among arts, science and Mathematics student's teacher in their mental health.…”
Section: Interpretation and Discussionsupporting
confidence: 93%
“…At 5% level of significance, the table value of 'F' is 3.02). It is inferred from the above table that calculates 'F' value (0.756) is lesser than the table value (3.00) for df(2, 297) and at 5% level of significance. Hence the null hypothesis is accepted.…”
mentioning
confidence: 69%
“…Second, both the adolescents and EPs experienced that EPs lack competencies to support adolescents with mental health problems. This finding corresponds to previous findings that EPs rate their training in mental health as inadequate, even though they themselves perceive it as part of their educating role to address mental health problems in their students and view the topic of student mental health as serious [29,[41][42][43]. However, these findings have not previously been confirmed from the perspective of the adolescents.…”
Section: Experiences With and Perspectives On Mental Health Help-seek...supporting
confidence: 79%
“…One study found that many early childhood educators felt that socioemotional development is mainly in uenced by events outside of their control (Papadopoulou et al, 2014). Another study found that while many earlychildhood educators desired the time and space to learn trauma intervention skills, those opportunities were commonly unattainable due to funding (Stein & Russell, 2021). Overall, it is clear this Birth-5 population is unique and has components needing analysis outside of the K-12 professional development system.…”
Section: Historical Foundationsmentioning
confidence: 99%
“…Previous research examining early-childhood educator populations shows there are systemic issues which deeply in uence the effectiveness of professional development trainings for this demographic (Papadopoulou et al, 2014;Stein & Russell, 2021). Funding is commonly highlighted as one of the top issues (Blewitt et al, 2021).…”
Section: Structural Issuesmentioning
confidence: 99%